2016
DOI: 10.3892/etm.2016.3782
|View full text |Cite
|
Sign up to set email alerts
|

Acroosteolysis in systemic sclerosis: An insight into hypoxia-related pathogenesis

Abstract: Abstract. Acro-osteolysis, or bony resorption of the terminal digital tufts, is a well-recognized, but under-researched, feature of systemic sclerosis. The mechanisms that disturbs local homeostatic balance of bone formation and resorption in favor of osteoclast activation and pathological bone loss remain to be established. Vascular alterations and reduced capillary density impair tissue oxygenation in systemic sclerosis, and the resulting hypoxia might contribute directly to the disease progression. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In scleroderma, acroosteolysis and condylysis are supposed to be caused by vasculopathy and pressure atrophy secondary to ischemia at the attachment site of muscles. 46 Although scleromyxedema generally does not present vasculopathy, our patient had several symptoms related to peripheral circulatory disorders such as coldness and numbness of her hands and feet since she developed skin manifestations. The microvascular impairment revealed by skin biopsy implies dermal/subcutaneous vascular loss and occlusion in her body.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In scleroderma, acroosteolysis and condylysis are supposed to be caused by vasculopathy and pressure atrophy secondary to ischemia at the attachment site of muscles. 46 Although scleromyxedema generally does not present vasculopathy, our patient had several symptoms related to peripheral circulatory disorders such as coldness and numbness of her hands and feet since she developed skin manifestations. The microvascular impairment revealed by skin biopsy implies dermal/subcutaneous vascular loss and occlusion in her body.…”
Section: Discussionmentioning
confidence: 76%
“…Bone resorption of the fingertips is characteristic of scleroderma, 4 and mandibles can also be affected in some cases. 5 However, no studies of scleromyxedema have reported these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is the master transcriptional regulator of the adaptive response to hypoxia, which is the tightly regulated form of HIF-1, and will quickly be hydroxylated and degraded in normoxic conditions by prolyl hydroxylases [34][35][36][37]. However, in hypoxia conditions, the expression of HIF-1α would dramatically upregulate [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The course is variable, with osteolysis stabilizing in some patients and progressing towards complete loss of the distal phalanges in others. Osteolysis in SSc is associated with more severe disease, including digital ulceration [25][26][27][28], pulmonary arterial hypertension (PAH) [24], severe digital ischemia [26][27][28], severe calcinosis [24,28,29], and longer disease duration [27,29]. Radiographic progression of flexion contractures has also been reported to be significantly higher in patients Fig.…”
Section: Systemic Sclerosismentioning
confidence: 99%